2019
DOI: 10.1039/c9na00317g
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Pd96Fe4 nanodendrites embedded in graphitic carbon nanosheets as highly efficient anode electrocatalysts

Abstract: Bimetallic Pd–Fe nanoalloys with tunable composition immobilized on graphitic carbon by one-pot radiolytic reduction show high electrocatalytic activity for alcohol oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 99 publications
1
16
0
Order By: Relevance
“…The most common catalysts that are usually applied in fuel cells for both electrodes are either pure platinum, Pt, or Ptenriched material as anode 13 since Pt nanomaterials S C H E M E 1 Possible products formed through GOR 8 deliberated as the most active electrocatalyst (Scheme 2). 14 However, Pt material is a scarce natural abundance 13,15,16 and poor resistance against poisonous species imposes significant limitations on its role, primarily when it deals with complex carbon-hydroxyl structure glycerol. 13,17 An expensive material with poor reaction kinetic and high loss of electrochemical surface area, such as Pt catalyst, becomes a hindrance toward DGFCs commercialization.…”
Section: Dgfcs' Challenge and Solutionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common catalysts that are usually applied in fuel cells for both electrodes are either pure platinum, Pt, or Ptenriched material as anode 13 since Pt nanomaterials S C H E M E 1 Possible products formed through GOR 8 deliberated as the most active electrocatalyst (Scheme 2). 14 However, Pt material is a scarce natural abundance 13,15,16 and poor resistance against poisonous species imposes significant limitations on its role, primarily when it deals with complex carbon-hydroxyl structure glycerol. 13,17 An expensive material with poor reaction kinetic and high loss of electrochemical surface area, such as Pt catalyst, becomes a hindrance toward DGFCs commercialization.…”
Section: Dgfcs' Challenge and Solutionmentioning
confidence: 99%
“…13,17 An expensive material with poor reaction kinetic and high loss of electrochemical surface area, such as Pt catalyst, becomes a hindrance toward DGFCs commercialization. 14,18,19 DGFC's strong reliance on the high-cost noble metal Pt usage 20 is an issue that needs to be solved. Developing low-cost catalysts with better kinetics for anodic electrooxidation and CO poisoning resistance is very desirable.…”
Section: Dgfcs' Challenge and Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up until now, it has been demonstrated that carbon supports such as carbon black, carbon nanotubes (CNTs), carbon fibers, mesoporous carbon, graphitic carbons, graphene etc. with suitable surface properties and functional groups can be used for metal NP deposition to fabricate efficient catalysts FCs [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, significantly lower interactions between hydrophobic surfaces of carbon supports with the catalyst and corrosion of supporting materials under experimental conditions hinder high catalytic activity and durability, which remain a significant challenge [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%